Aftermath of a Nuclear Attack : A Case Study on Post-Strike Operations - Chauhan, Anil (New Delhi Pentagon Press, 2010)
Effects of a nuclear strike and nuclear damage estimation --
Include Maps, Table, Appendix and Index
Keywords: Military policy -- Radioactivity--Physiological effect